2013
DOI: 10.1177/039463201302600423
|View full text |Cite
|
Sign up to set email alerts
|

Role of Steroid Therapy inPseudoxanthoma Elasticum-like Papillary Dermal Elastolysis

Abstract: Pseudoxanthoma Elasticum-Iike Papillary Dermal Elastolysis (PXE-PDE) is a peculiar idiopathic elastolytic disorder that clinically resembles Psudoxanthoma elasticum (PXE). It is histologically characterized by a total or partial loss of elastic fibers in the papillary dermis. It more often affects elderly women and is characterized by asymptomatic and symmetrical yellowish papules localized predominantly on the neck, supraclavicular regions, and flexural areas. After analyzing a series of cases and the recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Pseudoxanthoma elasticum‐like papillary dermal elastolysis is a rare idiopathic disorder affecting elderly women . Asymptomatic yellowish papules are situated symmetrically on the flexures, neck and supraclavicular areas and abdomen where it may resemble PXE. Dermoscopy reveals linear vessels and white‐yellow papules .…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoxanthoma elasticum‐like papillary dermal elastolysis is a rare idiopathic disorder affecting elderly women . Asymptomatic yellowish papules are situated symmetrically on the flexures, neck and supraclavicular areas and abdomen where it may resemble PXE. Dermoscopy reveals linear vessels and white‐yellow papules .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 40 cases of PXE-PDE have been reported in the literature. 1-9 PXE-PDE, an uncommon acquired skin disorder, exists on a spectrum of fibroelastolytic disease of the skin that includes variants such as mid-dermal elastolysis, upper dermal elastolysis, and white fibrous papulosis of the neck. A degree of clinical and histologic overlapping exists between the variants, making histopathology essential for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of PXE-PDE developing during therapy with methylprednisolone or triamcinolone for rheumatologic conditions highlight the potential effect of glucocorticoids in down-regulating the elastin gene expression and elastin messenger ribonucleic acid. 7,8…”
Section: Discussionmentioning
confidence: 99%
“…1,5,8 Another hypothesis holds that PXE-PDE is the result of abnormal elastic fiber formation, given the observation of immature fibers in the upper reticular dermis or evidence of activated fibroblastomas. 1,5 Pranteda et al 9 demonstrated that glucocorticoids may be involved in the pathogenesis of PXE-PDE, given their ability to reduce the expression of the elastin gene and its mRNA in human fibroblast cultures. 9 Even though PXE-PDE is an acquired condition, the case of 2 sisters 10 and the absence of cases in males suggests a genetic, hereditary, or hormonal factor that has not yet been identified.…”
mentioning
confidence: 99%
“…1,5 Pranteda et al 9 demonstrated that glucocorticoids may be involved in the pathogenesis of PXE-PDE, given their ability to reduce the expression of the elastin gene and its mRNA in human fibroblast cultures. 9 Even though PXE-PDE is an acquired condition, the case of 2 sisters 10 and the absence of cases in males suggests a genetic, hereditary, or hormonal factor that has not yet been identified.…”
mentioning
confidence: 99%